2021
DOI: 10.1155/2021/6666458
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation and Classification of Heart Angiographic Images Using Machine Learning Techniques

Abstract: Heart angiography is a test in which the concerned medical specialist identifies the abnormality in heart vessels. This type of diagnosis takes a lot of time by the concerned physician. In our proposed method, we segmented the interested regions of heart vessels and then classified. Segmentation and classification of heart angiography provides significant information for the physician as well as patient. Contradictorily, in the mention domain of heart angiography, the charge is prone to error, phase overwhelmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The evaluation revealed that the proposed system achieved an impressive area under the curve (AUC) of 0.99 after the second stage of classification. This indicates that the performance of the proposed system surpasses that of other systems that do not involve segmentation [25,26]. In recent statistics, it was reported that approximately 164,690 new cases of prostate cancer were diagnosed in 2018, resulting in about 29,430 deaths.…”
Section: Literature Surveymentioning
confidence: 84%
“…The evaluation revealed that the proposed system achieved an impressive area under the curve (AUC) of 0.99 after the second stage of classification. This indicates that the performance of the proposed system surpasses that of other systems that do not involve segmentation [25,26]. In recent statistics, it was reported that approximately 164,690 new cases of prostate cancer were diagnosed in 2018, resulting in about 29,430 deaths.…”
Section: Literature Surveymentioning
confidence: 84%
“…This deep learning approach used Inspire from the Di-Vnet network. The proposed model of deep learning predicts the disc coefficient is 90%, recall is 97%, precision is 92%, and accuracy of heart disease is 95% respectively [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…eir exploitation might result in the disappearance of financial gains and critical losses. Phishing attacks employ spam emails that attack online banking and money transfer accounts, all of which contain secret pins and passwords for user authentication, which is why hackers focus on banking and money transfer websites [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, this connectivity also serves as a gateway for malware, gray ware, and spyware. e GSM global communications expertise of another generation-2G enables the messaging among smartphones and sorted locations by exchanging the subsystem's replaced first-generation (1G) analog-centered facilities for a numerical, complete duplex and circuit substituted network for voice telephony [4]. GPRS 2.5-generation technology developed to improve the data rates and decrease the connection access time for 2G.…”
Section: Introductionmentioning
confidence: 99%